Maternal evasion: what policies do companies have been adopting in order to not lose their employees for maternity? A multicle study (Research, Society and Development, 2021)
This paper searches to identify the policies that are being adopted by companies to retain employees that are mothers, since the leaving of those professionals would result in several issues for the companies, once there are only few studies about this subject in the academic scenario. To do so, it was used the multiple case study method, through two interviews and two documents analysis, all of them in large companies. The data obtained was submitted to analysis by means of the categorization in an emergent manner, or else, the categories of analysis are derived from the results. Through this, three categories of analysis were created, however, the one category that concentrated the biggest highlight of these categories was the “types of benefits”. The results indicate that companies end up concentrating their benefits on specific points, very close to the legislation in force in each country, and do not use a business policies framework that could attend and retain their mother employees.